PENGARUH LOBI ISRAEL TERHADAP KEBIJAKAN LUAR NEGERI AS MENGENAI KONFLIK ISRAEL-PALESTINA PADA PEMERINTAHAN DONALD J. TRUMP (2016-2020) - Mayong Pambangkit (2022)
In the government of the United States of America, there is a political phenomenon known as lobbying. Lobbying is a group of organizations, groups or individuals working to influence policies to be taken by the United States government, be it domestic/domestic policies, as well as foreign policies. One of the most influential lobby groups in the United States government is the Israel Lobby. The Israeli lobby consists of organizations and individuals tasked with influencing US foreign policy to become pro-Israel in US foreign policy and international relations in the Middle East region. The Israel lobby can be a Jewish or non-Jewish organization. One of the US foreign policies that has been heavily influenced by the Israeli lobby is in dealing with the issue of the Israeli-Palestinian conflict. Throughout the history of the US government, and since the establishment of the state of Israel on May 14, 1948, the encouragement and support of the strong Israeli lobby has often made the US government's foreign policy more inclined and in favor of Israel. The Israel Lobby also keeps the US and Israel in bilateral relations very close and has resulted in much cooperation in the political, economic or military fields. In addition, Israel is the largest recipient of US foreign aid even though Israel is a developed and strong country economically and militarily in the Middle East Region. The pro-Israel attitude in US foreign policy was also shown during the administration of President Donald J. Trump (2016-2020). This research will focus on how the Israeli lobby influences US foreign policy regarding the Israeli-Palestinian conflict during the administration of Donald Trump and the policies that made by his administration